Ganesha with his consort, Indrani and Kaumari - Temples of India Project Team (Jio Institute, 2024)
Ganesha with his consort (left), Indrani (centre), and Kaumari (right) on the vedibandha (basal mouldings) of the Shiva Temple (Temple 3 in the site plan).